An Analysis of Student Learning Challenges in Elementary School Science Subject - Syahputra, Agus; Harahap, Risma Delima; Safitri, Islamiani (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2022)
The aimÂ of this study is to analyze the many aspects of learning challenges that elementary school students encounter when learning science. The method of research was descriptive with a qualitative focus. All theÂ students inÂ classes IV, V, and VI were employed as research subjects. The researcher served as the instrument in this study, supplemented by interview, observation, and documentation criteria, while data analysis was accomplished through data reduction, presentation, and conclusion. As a result of the research, the largest degree of difficulty encountered by theÂ students was with school facilities and infrastructure, at 96.73%, while the second highest level was with the learning media used by theÂ teachers, at 82.45%. The next highest level was the indication of student interest in science lessons, which had a percentage value of 75%. This was because some students still did not comprehend how science was taught, as indicated by the lowest score of 73.90%. The existence of theÂ challenges in science learning had a significant impact on student interest in learning andÂ understanding level, resulting in a less effective teaching and learning process in the classroom. The solution to the above problems is for the teacher to obtain a better understanding of the students’Â needs while they are studying, for the teacher to employ a variety of learning media that entice students to learn, and for the principal to provide comprehensive facilities that support positive learning outcomes.